Impact of the Affordable Care Act on health insurance access, coverage, and cost for refugees resettled in the USA - Dr. P Agrawal, MD; A K Venkatesh, MD (Elsevier, 2015)
Background: Refugees arriving in the USA are a vulnerable population with limited access to health insurance. The Affordable Care Act (ACA) has been heralded as an opportunity to reduce health-care disparities by improving access to health insurance. However there is substantial between-state variation with respect to enactment of Medicaid expansion and implementation of health-care insurance exchanges. We sought to describe the relation between 2012 refugee resettlement patterns and health-care insurance improvements created by the ACA. Methods: We conducted a cross-sectional analysis of 2012 refugee resettlement data from all 50 states and the District of Columbia. We obtained data from the Office of Refugee Resettlement, the Kaiser Family Foundation, and the US Government health insurance website healthcare.gov. We compared resettlement data for states that have expanded Medicaid and implemented Health Insurance Exchange schemes and those that have not. We used the Wilcoxon rank sum test to investigate whether there was a relation between the price of insurance policies in each state and refugee resettlement rates there. Findings: In 2012, 58 238 refugees from 85 countries were resettled in the USA. 32 389 refugees were resettled to 27 states that expanded Medicaid coverage under the ACA (median 555, range 0-5173 refugees per state). This rate did not differ from that for the 25 849 refugees who were resettled to 24 states not expanding Medicaid coverage (median 775 [0-5293]; p=0·7341). The median number of refugees resettled to the 17 states creating health insurance exchanges was 817 (1-5173), which was no higher than the median number of refugees resettled to the 34 states using the federal insurance exchange (601 [0-5923]; p=0·4906). The median monthly premium for a bronze health insurance plan did not differ between states with insurance exchanges ($232) and states with only the federal exchange ($264; p=0·1365). Interpretation: In 2012, more refugees were resettled to states that have not expanded Medicaid or created state health insurance exchanges. Because many states have small or no refugee resettlement programmes, the difference in distribution of resettlement based on state insurance policies does not reach statistical significance. Future research should explore the effect of these differences in state policies on refugee health outcomes. Policymakers should consider between-state variation in access to insurance when devising refugee resettlement strategies. Funding: None.